Experimental evaluation of conducted disturbances induced during high frequency switching of active components - Slimani, Helima; Zeghoudi, Abdelhakim; Bendaoud, Abdelber; Bechekir, Seyfeddine (Національний технічний університет "Харківський політехнічний інститут", 2023)
Power electronics devices are among the most widely used equipment in all fields. The increasing performance of these devices makes their electromagnetic interference factor very important. On the other hand, electromagnetic compatibility research is more and more interested in studies on the sources of electromagnetic disturbances, their propagation paths and the methods of reducing these electromagnetic disturbances. The purpose is to study the behavior of the various active power components at high frequency as well as the evaluation of their electromagnetic noise by using simulation and experimental measurement. Methods. In first time, the simulation was realized with the Lt-spice software which presents many advantages in its use and we validate in the second time the results obtained with experimental measurements. We start by study of the behavior of the diode, then the behavior of MOSFET transistor and finally the study of the behavior of the IGBT transistor. Results. All the simulations were performed using the Lt-spice software and the results obtained are validated by experimental measurements performed in the APELEC Laboratory at the University of Sidi Bel-Abbes in Algeria. The waveforms of the current and voltage across each component during its opening are presented. The results of the simulations are compared and validated with the realized measurements in order to better present the influence of the fast switching of semiconductors on the electrical quantities, which causes electromagnetic disturbances in the interconnected electrical system.

Пристрої силової електроніки знаходяться серед обладнання, що найбільш широко використовується у всіх областях. Підвищення продуктивності цих пристроїв робить фактор їх електромагнітних перешкод дуже важливим. З іншого боку, при дослідженні електромагнітної сумісності дедалі більше цікавляться джерелами електромагнітних перешкод, шляхів їх поширення та методами зменшення цих електромагнітних перешкод. Мета роботи полягає в тому, щоб вивчити поведінку різних компонентів активної потужності на високих частотах, а також оцінити їхній електромагнітний шум за допомогою моделювання та експериментальних вимірювань. Методи. Уперше моделювання було реалізовано за допомогою програмного забезпечення Lt-spice, яке дає багато переваг при його використанні, і вдруге ми підтверджуємо результати, отримані за допомогою експериментальних вимірів. Ми починаємо з вивчення поведінки діода, потім поведінки MOSFET транзистора і, нарешті, вивчення поведінки IGBT транзистора. Результати. Усі моделювання були виконані з використанням програмного забезпечення Lt-spice, а отримані результати підтверджені експериментальними вимірами, проведеними в лабораторії APELEC в Університеті Сіді-Бель-Аббес в Алжирі. Представлені осцилограми струму та напруги на кожному компоненті під час його відкриття. Результати моделювання порівнюються та підтверджуються реалізованими вимірами, щоб краще уявити вплив швидкого перемикання напівпровідників на електричні величини, що викликає електромагнітні перешкоди у взаємозалежній електричній системі.
Keywords: electromagnetic compatibility; electromagnetic disturbances; high frequency switching of active components; experimental measurement; електромагнітна сумісність; електромагнітні перешкоди; високочастотне перемикання активних елементів; експериментальне вимірювання